2010
DOI: 10.1016/j.apgeochem.2010.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of gypsum with lead in aqueous solutions

Abstract: Sorption processes on mineral surfaces are a critical factor in controlling the distribution and accumula tion of potentially harmful metals in the environment. This work investigates the effectiveness of gypsum This study shows that the surface of gypsum can play an important role in the attenuation of Pb in contaminated waters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 23 publications
1
25
0
Order By: Relevance
“…Among sedimentary rock-forming minerals, calcium sulfates, and more specifically gypsum (CaSO 4 Á2H 2 O) and anhydrite (CaSO 4 ), emerge as potentially useful minerals to take up, via dissolutionprecipitation mechanisms, dissolved metals. Indeed, Astilleros et al (2010), investigating the uptake of Pb by gypsum (K sp =10 À4.48 ), concluded that this mineral has a remarkable capac-ity to remove Pb (aq) from highly contaminated aqueous solutions via the formation of the solid phase anglesite (PbSO 4 ). A close inspec-tion of the gypsum surfaces evidenced that anglesite crystals are located in a random orientation with respect to the gypsum sub-strate.…”
Section: Introductionmentioning
confidence: 99%
“…Among sedimentary rock-forming minerals, calcium sulfates, and more specifically gypsum (CaSO 4 Á2H 2 O) and anhydrite (CaSO 4 ), emerge as potentially useful minerals to take up, via dissolutionprecipitation mechanisms, dissolved metals. Indeed, Astilleros et al (2010), investigating the uptake of Pb by gypsum (K sp =10 À4.48 ), concluded that this mineral has a remarkable capac-ity to remove Pb (aq) from highly contaminated aqueous solutions via the formation of the solid phase anglesite (PbSO 4 ). A close inspec-tion of the gypsum surfaces evidenced that anglesite crystals are located in a random orientation with respect to the gypsum sub-strate.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of background electrolytes has also been shown to affect the growth features of gypsum {010} surfaces . Coupled dissolution-crystallization reactions starting with gypsum as the parent solid were observed by Astilleros et al (2007), who investigated the interaction between gypsum and Pb-bearing aqueous solutions. Combining macroscopic experiments and in situ AFM observations, these authors showed that the dissolution of gypsum is accompanied by the precipitation of anglesite * E-mail: eruiz_01@uni-muenster.de (PbSO 4 ), and that gypsum may represent an efficient tool for the sequestration of Pb.…”
mentioning
confidence: 99%
“…The initial pH value of 4.5 for solution containing 6000ppm of Pb 2+ increased slightly during the first interaction time, and reached a constant value of 5.6. This may be due to the formation of anglesite (PbSO4), and the release of Ca 2+ which is more basic than Pb 2+ , as previously found by Astilleros et al (2010) [12].…”
Section: Adsorption Isothermsmentioning
confidence: 68%